2011
DOI: 10.1088/0953-4075/44/13/135101
|View full text |Cite
|
Sign up to set email alerts
|

Structural and electronic properties of boron- and nitrogen-doped SinCn(n= 7–15) clusters: a theoretical investigation

Abstract: The structural and electronic properties of SinCn (n = 7–15) cage-like clusters doped with boron and nitrogen atoms have been investigated using spin-polarized density functional calculations. We found that the B@SinCn and N@SinCn clusters energetically favour cage-like structures, and the B/N dopant prefers to be located at the interior/surface site of the Si frame. Theoretical results indicate that four clusters are highly stable, which are B@Si8C8, N@Si14C14, N@Si8C8, and N@Si12C12 clusters. On the basis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…A novel type of nanostructure, SiC, has attracted a rising number of attentions. Amount of experimental and theoretical investigations have shown that, regardless of the form of nanotube or nanocluster, the pure SiC systems have considerable application potential. They may be used in high power, high temperature and high‐frequency devices because of their unique electrical, thermal, and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…A novel type of nanostructure, SiC, has attracted a rising number of attentions. Amount of experimental and theoretical investigations have shown that, regardless of the form of nanotube or nanocluster, the pure SiC systems have considerable application potential. They may be used in high power, high temperature and high‐frequency devices because of their unique electrical, thermal, and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%